Implementasi Personal Selling Sebagai Strategi Komunikasi Pemasaran Dalam Membentuk Brand Image Greenpro - Irvan Supriyanto; Rindana Intan Emeilia (CV. ITTC INDONESIA, 2024)
Marketing communication is an important part of business. Effective marketing communication greatly helps companies in increasing market share. In this effort, companies need to use marketing communication strategies, one of which is personal selling. Personal selling is face to face marketing method so that sales are created and can build trust and attachment to potential buyers. The purpose of the study is to find out how to implement personal selling as a marketing communication strategy in shaping the brand image of Greenpro. This study uses a descriptive qualitative method. The results of the study show that the implementation of personal selling is carried out using retail selling in building the brand image of Greenpro products. The research results also show that GreenPro uses the personal selling stages used in forming the Greenpro brand image starting from selecting consumers, pre-approaching, approaching, presenting, overcoming objections, closing and customer follow-up